2017
DOI: 10.1016/j.cellimm.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol (CBD) induces functional Tregs in response to low-level T cell activation

Abstract: Many effects of the non-psychoactive cannabinoid, cannabidiol (CBD), have been described in immune responses induced by strong immunological stimuli. It has also been shown that CBD enhances IL-2 production in response to low-level T cell stimulation. Since IL-2, in combination with TGF-β1, are critical for Treg induction, we hypothesized that CBD would induce CD4+CD25+FOXP3+ Tregs in response to low-level stimulation. Low-level T cell stimulation conditions were established based on minimal CD25 expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 44 publications
1
28
0
1
Order By: Relevance
“…153 We showed in vitro that CBD (1-15 lM) induced functional CD4 + CD25 + Foxp3 + T cells under conditions of suboptimal stimulation and that Il10 mRNA expression was induced. 154 There are only a few studies in which B cells are identified as targets of CBD. CBD given at 25 mg/kg by intraperitoneal (i.p.)…”
Section: Cbd Effects and Mechanisms Of Immune Suppression In Lymphocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…153 We showed in vitro that CBD (1-15 lM) induced functional CD4 + CD25 + Foxp3 + T cells under conditions of suboptimal stimulation and that Il10 mRNA expression was induced. 154 There are only a few studies in which B cells are identified as targets of CBD. CBD given at 25 mg/kg by intraperitoneal (i.p.)…”
Section: Cbd Effects and Mechanisms Of Immune Suppression In Lymphocytesmentioning
confidence: 99%
“…Indeed, studies from our laboratory and others have shown that CBD either enhanced or suppressed cytokine production (IL-2 and IFN-c) in response to relatively low or high degree of immune stimulation, respectively. 154,179,180 The mechanism for the differential responsiveness likely involves alterations in intracellular calcium, as CBD increases intracellular calcium in mouse splenocytes regardless of the increase of intracellular calcium produced by the immune stimulant. 179 In addition, the differential cytokine production was correlated with nuclear expression of the NFAT transcription factor, 179 which is calcium responsive.…”
Section: Nichols and Kaplanmentioning
confidence: 99%
See 1 more Smart Citation
“…[27] Immunomodulatory effects CBD modulated T-cell function and apoptotic signaling pathway. [28] Inflammatory bowel disease (IBD) CBD attenuated intestinal inflammation and normalized motility in patients with IBD. [29] Cognitive impairments CBD interacted with components of emotional memory processing and memory-rescuing, as well as attenuated THC-induced memory impairment effects.…”
Section: Research Themes Main Findings Referencesmentioning
confidence: 99%
“…Excess PBS was added to stop the enzymatic reaction, and the tissue was minced and meshed on 70 μm filters. Immunofluorescence staining was performed as our previous methods [11]. Briefly, cells were incubated with Fc block solution (purified anti-mouse CD16/CD32, clone 2.4G2, BD Biosciences) for 15 min at room temperature to prevent non-specific binding.…”
Section: Flow Cytometrymentioning
confidence: 99%